Inclúyase un numeral al artículo 79 del código de la niñez y adolescencia, en donde exista la protección integral al niño, niña o adolescente que haya sufrido maltrato, abuso o explotación sexual en un centro de educación - Espinoza González, Wendy Paola (2017)
The Constitution of the Republic in its article 46 paragraph 4 states that the State shall, inter alia, the following measures to ensure the children and adolescent care and protection against all forms of violence, abuse, sexual exploitation or any other nature, or against negligence causing such situations. Similarly article 66 paragraph 9 of the same legal body recognizes and ensure people: The right to make free, informed, voluntary and responsible about their sexuality, and life and sexual orientation. The State shall promote access to the means to make these decisions are made under safe conditions. Also within the purview of the Code of Children and Adolescents, the protection of the right to freedom and sexual integrity of children and adolescents is given, however there are some inconsistencies as provided for in Article 41 of the legal body He states: "Sanctions prohibidas.- educational establishments is prohibited application: 1. Bodily Sanctions; 2. Sanctions psychological undermining human dignity of children and adolescents; 3. collective punishments are prohibited; Y, 4. Measures involving exclusion or discrimination because of a personal condition of the student, parent, or legal representatives who have it in their care. discriminatory measures because of pregnancy or maternity of a teenager are included in this prohibition. A no child or adolescent may be denied registration or expelled because of the status of their parents. In any legal proceedings aimed at establishing the responsibility of a child or adolescent by a lack of discipline in an educational institution, the right to defense of the student and their parents or guardians be guaranteed. Any form of sexual assault in educational establishments will be made known to the competent prosecutor, for the purposes of the Act, subject to the investigations and administrative sanctions that apply in education ". Furthermore Article 79 of that code says protective measures against mistreatment, abuse, sexual exploitation, trafficking and loss of children and adolescents; specifically in paragraphs 11 and 12 points respectively: 11. Suspension of the operation of the entity or establishment where the institutional abuse occurred, as long as the conditions justifying the action; 12. Participation of the aggressor or staff of the institution in which institutional abuse has occurred in workshops, courses or any form of training events ... .; In emergency cases that provide strong indications of aggression or threat of physical, psychological or sexual integrity of the child or adolescent or flagrante delicto care entities authorized may provisionally implement the measures of paragraphs 2 to 9, 12 and 13, and make it known to the competent authority within a maximum period of seventy two hours, so that you have the definitive measures. As we can see in the Code of Childhood and Adolescence, there lenient sanctions for educational institutions, as well as the person or persons who committed abuse or sexual exploitation; for that reason it should be a legal reform to Article 79 of the Code of Children and Adolescents, for staff of the educational institution or the minor's parents, brought to the attention of the competent authority within twenty-four hours mistreatment , sexual abuse or exploitation has been given; and the child or adolescent immediately receive psychological care.